Analisis Pengaruh Produksi Karet, Luas Areal dan Harga terhadap Produk Domestik Regional Bruto (PDRB) Sektor Perkebunan Tahun 2010-2019 Kabupaten Tanah Bumbu - Nimang Triani Haryati; Chairul Sa’roni (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to (1) analyze how much influence the production of rubber has on the GRDP of the plantation sector in Tanah Bumbu Regency, (2) analysis how big the influence of the area on the GRDP of the plantation sector in Tanah Bumbu Regency (3) analyze how much influence the price has on the GRDP of the plantation sector in Tanah Bumbu Regency. The period of the year used and the years 2010 to 2019.The data analysis technique used is multiple linear regression analysis using the method of least squares (Ordina Least Square) to analyze how much the influence of the independent variable on the dependent variable. Based on the type of research used in this research is quantitative analysis, with the source of data collection. The type of data used in this research is secondary data.The results of this study are(1) showing rubber production, area, and rubber price have a significant effect simultaneously on the GRDP of the Plantation Sector in the District Tanah Bumbu, (2) show the results of this study that the area is a factor the largest production has a positive and significant effect on the GRDP of the Sector Plantations in Tanah Bumbu District.